Omental Torsion in a Child a Case Report - Baker, A; Uddin, AKM Helal; Karim, MS (Pulse, 2014)
Omental torsion, a very rare cause of acute abdominal pain, mimicking acute appendicitis .A boy of 11 years, presented to us with the symptoms and signs suggestive of acute appendicitis clinically, was admitted through OPD of Apollo Hospitals. His laboratory reports were also in favor of clinical diagnosis. Laparoscopic appendicectomy was planned. But on laparoscopic intra-abdominal inspection it was found to be a case of Omental torsion, distal part was closely adherent to the ascending colon and blackish in color. So, procedure was converted into laparotomy and resection of the tensioned and gangrenous part of the omentum including appendicectomy was done. His post operative period was uneventful. Although torsion of the omentum is a rare clinical entity, but accurate pre-operative clinical assessment and relevant study including imaging and CT abdomen may reduce the diagnostic dilemma between omental torsion and acute appendicitis. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20360 Pulse Vol.6 January-December 2013 p.75-77